2022
DOI: 10.3389/fcell.2022.999600
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar type 2 epithelial cell senescence and radiation-induced pulmonary fibrosis

Abstract: Radiation-induced pulmonary fibrosis (RIPF) is a chronic and progressive respiratory tract disease characterized by collagen deposition. The pathogenesis of RIPF is still unclear. Type 2 alveolar epithelial cells (AT2), the essential cells that maintain the structure and function of lung tissue, are crucial for developing pulmonary fibrosis. Recent studies indicate the critical role of AT2 cell senescence during the onset and progression of RIPF. In addition, clearance of senescent AT2 cells and treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…ATII cells are one of the critical target cells for lung IRI that are involved in neutrophil chemotaxis and their dysfunction is a vital effector process of lung injury (22). In vitro studies were performed using ATII epithelial cells to investigate cell specific signaling mediated by LxA 4 in a FPR2-dependent manner ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…ATII cells are one of the critical target cells for lung IRI that are involved in neutrophil chemotaxis and their dysfunction is a vital effector process of lung injury (22). In vitro studies were performed using ATII epithelial cells to investigate cell specific signaling mediated by LxA 4 in a FPR2-dependent manner ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, radiation can cause DNA damage, resulting in cell cycle arrest and cell senescence. Previous studies have shown that alveolar epithelial cell senescence is also a key factor in PF 41 . Furthermore, studies have suggested that DSB repair may be involved in fibrosis 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that alveolar epithelial cell senescence is also a key factor in PF. 41 Furthermore, studies have suggested that DSB repair may be involved in fibrosis. 42,43 EMTassociated transcription factors may also regulate DSB repair, [44][45][46][47][48] indicating that there may be crosstalk between DSB repair and EMT, and the role of DNA-PKcs-mediated regulation of DSB repair and senescence in alveolar epithelial cells in RIPF needs to be further elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia increases ROS production, regulates TGF-β, and promotes collagen formation, thereby reducing alveolar elasticity [ 20 ]. In addition, ROS can cause cell loss, alveolar wall edema, increased vascular permeability, and protein exudation, further reducing lung elasticity, destroying vascular integrity, and increasing the apoptosis of alveolar type I epithelial cells, thereby promoting alveolar type II epithelial cell proliferation and aggravating lung inflammation [ 10 , 21 ]. Under long-term cytokine action, fibroblast recruitment and myofibroblast proliferation lead to the remodeling of the extracellular matrix (ECM) and epithelial-mesenchymal transition (EMT), resulting in fibrogenesis and scar formation, eventually replacing the normal lung tissue with the development of advanced PF [ 22 , 23 ].…”
Section: The Mechanisms Of Radiation-induced Lung Injurymentioning
confidence: 99%